Ground contact time as an indicator of metabolic cost in elite distance runners - Chapman, R. F.; Laymon, A. S.; Wilhite, D. P.; McKenzie, J. M.; Tanner, D. A.; Stager, J. M. (Medicine & Science in Sports & Exercise, 2012)
Differences in running economy at common speeds have been demonstrated between male and female distance runners, as well as between middle-distance (MD) and long-distance (LD) specialists. Whether measures of foot ground contact time (tc), known to be proportional to the mass-specific cost of locomotion, follows the same running economy relationships in these groups is unknown.